2020
DOI: 10.1186/s13148-020-0818-7
|View full text |Cite
|
Sign up to set email alerts
|

H3K27me3 and EZH2 expression in melanoma: relevance for melanoma progression and response to immune checkpoint blockade

Abstract: Background: Upregulation of the histone methyltransferase enzyme EZH2 and its histone modification H3K27me3 has been linked to melanoma progression, metastasis, and resistance to immune checkpoint blockade (ICB). In clinical trials, EZH2 inhibitors are currently tested to overcome resistance to ICB. The aim of this study is to evaluate expression patterns and the predictive value of H3K27me3 and EZH2 in metastatic melanoma samples prior to ICB. As H3K27me3 expression has been associated with a dedifferentiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Our data supports that proteomic profiling of histone methylation levels improves outcome prediction in AML and Ph+ ALL and suggest potential targets to further investigate diagnostically and therapeutically. H3K27me3 loss associates with tumor aggressiveness and patient outcomes in numerous cancers [ 10 16 ], similar as we found in AML.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Our data supports that proteomic profiling of histone methylation levels improves outcome prediction in AML and Ph+ ALL and suggest potential targets to further investigate diagnostically and therapeutically. H3K27me3 loss associates with tumor aggressiveness and patient outcomes in numerous cancers [ 10 16 ], similar as we found in AML.…”
Section: Resultssupporting
confidence: 84%
“…Epigenetic dysregulation by histone protein modifications is also well-recognized to play a role in tumor development. Loss of the repressive mark H3K27me3 has been reported in breast, colon, ovarian, pancreatic, prostate, nervous system tumors and melanoma [ 10 16 ]. H3K4 di- and trimethylation are associated with open and active chromatin and are predictive factors for outcome in different cancers with low expression of H3K4me2 being associated with poor outcome in prostate, kidney and lung cancer and high expression of H3K4me3 in liver and cervical cancer [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The co-operative binding of PRC1 (including the BMI1 subunit) and the long noncoding RNA ANRIL to H3K27me3 compacts the CDKN2A genomic locus and represses transcription [ 25 , 30 , 31 , 32 ], in particular the transcription of p16 INK4a [ 33 ]. In line with these data, the levels of H3K27me3 increase from primary to metastatic melanoma, and high H3K27me3 is an independent poor prognostic marker in melanoma [ 34 , 35 ].…”
Section: Somatic Cdkn2a Alterations In Melanomamentioning
confidence: 78%
“…The polycomb repressor complex 2 (PRC2) core component molecule EZH2 has been reported to be important in biological processes, such as the cell cycle, cell differentiation, and carcinoma progression [40,41]. Previous studies showed that EZH2 was significantly increased in NB and negatively associated with NB prognosis [42].…”
Section: Discussionmentioning
confidence: 99%